The long-term transformation of the concept of CSR: Towards a more comprehensive emphasis on sustainability - Hildegunn Mellesmo Aslaksen; Clare Hildebrandt; Hans Christian Garmann Johnsen (International Journal of Corporate Social Responsibility (JCSR), 2021)
This article adds to the discussion of the long-term transformation of CSR, presenting a perspective on the interplay between CSR debate and public discourse on business responsibility. 50 years after Milton Friedman's provoking claim that the only responsibility for business is to seek profit, a broader debate has emerged aligning CSR with an increasingly comprehensive concept of sustainability. We trace this evolution of the concept during the last three decades focusing on the intersection of economic, social, and environmental responsibility. Based on discourse analysis of news articles and opinion pieces in the largest public newspaper in Norway from 1990 until 2018, the study confirms that discussions on CSR, sustainability and the social model often approach the same challenges. We argue that sustainability has become the dominating term in popular usage for describing the relationship between business and society. Based on our analysis of the public debate, CSR has become a more comprehensive term, transformed from being a term mainly related to internal business affairs to part of a broader societal discussion about sustainability.
Keywords: 650; CSR; Sustainability; Social model; Discourse; Business-society relationship